2012
DOI: 10.1166/jnn.2012.5342
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline Silicon Films with Nanometer-Sized Dense Fine Grains Formed by Flash-Lamp-Induced Crystallization

Abstract: Flash lamp annealing (FLA) with millisecond-order pulse duration can crystallize microm-order-thick a-Si films on glass substrates through explosive crystallization (EC), and flash-lamp-crystallized (FLC) poly-Si films consist of densely-packed nanometer-sized fine grains. We investigate the impact of the hydrogen concentration and the defect density of precursor a-Si films on crystallization mechanism and the microstructures of FLC poly-Si films, by comparing chemical-vapor-deposited (CVD) and sputtered precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…3. The amount of H atoms in Cat-CVD a-Si films probably has no significant impact on the mechanism of EC, since EC leaving behind periodic structures occurs also in sputtered a-Si films containing little H atoms [9]. It should be noted that the formation of Cat-CVD a-Si films with similar tensile stress has also been reported by Mahan [19], which is realized by systematically changing H 2 flow rate.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 58%
See 2 more Smart Citations
“…3. The amount of H atoms in Cat-CVD a-Si films probably has no significant impact on the mechanism of EC, since EC leaving behind periodic structures occurs also in sputtered a-Si films containing little H atoms [9]. It should be noted that the formation of Cat-CVD a-Si films with similar tensile stress has also been reported by Mahan [19], which is realized by systematically changing H 2 flow rate.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 58%
“…Cat-CVD can yield a-Si films with lower film stress than conventional plasma-enhanced CVD (PECVD). We have also revealed that the crystallization of a-Si films induced by FLA is based on explosive crystallization (EC), self-catalytic lateral crystallization driven by the release of latent heat [8][9][10][11][12]. To date, we have observed at least two modes of EC: 1) EC forming poly-Si films with periodic microstructures along a lateral crystallization direction containing solid-phase-nucleated (SPN) 10-nm-sized fine grains, and 2) EC based on liquid-phase epitaxy (LPE) which results in the formation of poly-Si films consisting only of large grains with a length of N10 μm stretching along an EC direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of a variety of process techniques to form poly-Si films, the annealing of precursor a-Si films for crystallization by rapid treatment has been expected to be one of the most productive methods. We have so far investigated the crystallization of a-Si films on glass substrates by FLA, an annealing technique using millisecond-order discharge from Xe lamps [1][2][3][4][5]. Due to its proper annealing duration, µm-order-thick a-Si films can be crystallized without serious thermal damage onto whole glass substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the method of a-Si preparation, at least two kinds of EC can occur: one is EC governed by frequent solid-phase nucleation leaving behind periodic microstructures, and the other is EC only through LPE. The former EC occurs when sputtered or catalytic chemical vapor deposited (Cat-CVD) a-Si films are used [1][2][3], while the latter EC is seen if we use EB-evaporated a-Si films as precursors [4,5]. We can obtain larger grains in the latter case due to less frequent nucleation, which would lead to reduction in carrier recombination on grain boundaries and thus contribute to improvement in solar cell properties.…”
Section: Introductionmentioning
confidence: 99%